"I have to go the extra mile". How fat female employees manage their stigmatized identity at work. Issue 1 (March 2019) - van Amsterdam, Noortje; van Eck, Dide
Highlights: Body size is a marker of diversity in organizations that intersects with gender. Fatness is constructed through healthism and obesity discourse as a moral issue. Fat female employees engage in identity work to manage fat stigma. Managing fat stigma increases the workload for fat employees. Identity work involves both narrative and embodied strategies. Abstract: This study explores how fat female employees engage in identity work to manage stigmatizing expectations grounded in healthism and obesity discourse that construct fat people as unhealthy, stupid, unprofessional, and lazy. We interviewed 22 women who self-identified as fat, full-figured or obese. Our analysis reveals how our participants engaged in identity work strategies in order to project a professional appearance and highlight their work performances. Many strategies reproduced dominant notions about fatness such as 'smartening up', 'distracting', 'hiding', 'concealing', 'humour', 'compensating', 'explaining' and 'defensive Othering'. Yet at times some participants also used strategies that challenged dominant discourses about size, such as 'flaunting', 'irony' and 'self-acceptance'. The identity work strategies our participants engaged in were not just narrative; many involved what they did with their bodies. We therefore argue the need for further theorizing embodied identity work, specifically with regards to how size matters in the context of employment.